Auto-transplantation for anterior tooth replacement - A/Prof Ji Young Yoon; Prof Yong Hoon Choi (Elsevier, 2023)
Introduction: When extraction of the maxillary anterior tooth is necessary and not optional, a clinician must choose treatment options such as bridge or dental implant to restore aesthetics and functions that the tooth offers. In this report, an auto-transplantation of maxillary third molar was used for anterior tooth replacement. Case Description: A 38-year-old male visited the Department of Operative Dentistry in Seoul National University Budang Hospital with a chief complaint of horizontal root fracture on a left maxillary central incisor. The tooth was decided to be extracted, and various conventional treatment methods including bridge and dental implant were explained to the patient. The patient had microdontia in maxillary third molars areas and CBCT images verified that the dimensional sizes of microdontia and central incisor roots were similar. Thus auto-transplantation was also explained as an alternative option and chosen by the patient. The surgical procedures proceeded with a series of protocols and endodontic and prosthodontic treatments were followed. Discussion: If a patient with missing anterior tooth has a microdontia on the maxillary third molar area, auto-trasnplantation could be considered as a valid treatment option. For a successful treatment, there are some considerations.1. The precise pre-operative evaluation through oral exams and CBCT images is necessary.2. Delicate surgical procedures including atraumatic extraction and short extra-oral treatment time are important.3. After the surgical procedures, resin-wire splinting, root canal treatment and esthetic prothesis should be followed. Conclusion/Clinical Significance: With a precise pre-operative evaluation and delicate surgical management, auto-transplantation could be an alternative treatment option for anterior tooth replacement to a patient with microdontia.